Diagnostic assessment of autism in adults – current considerations in neurodevelopmentally informed professional learning with reference to ADOS-2 - Curnow, Eleanor; Utley, Izy; Rutherford, Marion; Johnston, Lorna; Maciver, Donald (Frontiers in Psychiatry, 2023)
Services for the assessment and diagnosis of autism in adults in the United Kingdom have been widely criticised and there is an identified need for further research in this field. There is a call for diagnostic services to become more accessible, person-centred, neurodiversity affirming, and respectful. In Scotland, there is a need for workforce development which will increase capacity for diagnostic assessment and support for adults. ADOS-2 is a gold-standard diagnostic assessment tool for autism recommended in clinical guidelines. However, diagnostic procedures such as the ADOS-2 are rooted in the medical model and do not always sit comfortably alongside the neurodiversity paradigm preferred by the autistic community. Training and educational materials need to account for the differences between these approaches and support clinicians to provide services which meet the needs of the adults they serve. The National Autism Implementation Team work alongside ADOS-2 training providers to support clinicians in Scotland, to provide effective diagnostic assessment within a respectful environment. The team engaged with clinicians who had attended ADOS training to identify areas of uncertainty or concern. Training materials were developed to support ADOS assessors to incorporate key principles including 'nothing about us without us;' 'difference not deficit;' 'environment first;' 'diagnosis matters,' 'language and mindsets matter;' and 'a neurodevelopmental lens,' to support the provision of neurodiversity affirming practice. The National Autism Implementation Team also provided examples of actions which can be undertaken by clinicians to enhance the assessment experience. Training materials are based on research evidence and clinical experience.